THE ROLE OF ACCOUNTING INFORMATION SYSTEMS IN THE DEVELOPMENT OF ERP IN INDONESIA - Amrih, Gilang Ganjar; Maryani, Leni (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyse the role of accounting information systems (AIS) in the development and implementation of Enterprise Resource Planning (ERP) in Indonesia using a descriptive empirical approach. Data was obtained from industry reports, government documents, ERP company publications, and recent academic studies. The results show that AIS is a core component in the success of ERP because it supports financial data integration, reporting accuracy, and internal control. Large companies in the manufacturing, finance, and retail sectors have benefited significantly from ERP, while MSMEs and government agencies still face challenges related to digital literacy, human resource readiness, and technological infrastructure. This study concludes that ERP success depends on technological readiness, user competence, and change management strategies. These findings contribute to the digital accounting literature and have practical implications for strengthening digital transformation in Indonesia